UARS MLS HNO 3 Observations: Implications for Antarctic PSCs - Santee, M. L.; Tabazadeh, A.; Manney, G. L.; Salawitch, R. J.; Froidevaux, L.; Read, W. G.; Waters, J. W. (2004)
We present Microwave Limb Sounder (MLS) measurements fo gas-phase HNO 3 obtained at the beginning of five southern hemisphere winters.